Simulasi Dan Analisis Quality Of Service Audio File Sharing Pada Jaringan Vanet Dengan Menggunakan Protokol Vadd - Yeska Haganta; Agus Virgono; Randy Erfa Saputra (eProceedings of Engineering, 2018)
Abstrak Hiburan merupakan salah satu aspek terpenting dalam kehidupan manusia. Hiburan dapat berupa gambar, suara, animasi, dan lain-lain. Pada saat ini, semua aspek hiburan dikemas dalam sebuah teknologi bernama Internet. Internet mempunyai banyak manfaat seperti mendapatkan informasi, kemudahan berkomunikasi, dan sarana hiburan. Internet sendiri sudah mengalami pekembangan yang sangat pesat, dan mengarah kepada sambungan tanpa kabel (wireless connection). Perkembangan teknologi Internet, yang disertai dengan pertumbuhan kendaraan Hasil simulasi menunjukan bahwa average end-to-end packet delivery delay mempunyai nilai yang bervariasi dari terendah 105.301 ms – 137.8 ms untuk semua ukuran audio file, dan nilai throughput yang bervariasi dari 8.846 Mbps – 299.999 Mbps Kata kunci : Artificial Intelligence, Sistem Pakar, Forward Chaining, Certainty Factor Abstract At this moment, Internet is one of the most important parts of our lives. By Internet, we can get various information easily, throughout data communications, such as sending a message, file sharing, and many others. Technology of data communication has encounter many developments, followed by rapid growth of vehicle in the worldwide, create a new technology, which called VANET. VANET is a technology, which uses vehicle as node in ad-hoc network. VANET itself has many benefits, such as collision warning, file-sharing, and many others. On this final project, I did a simulation of audio file transmission, in form of lossy and loseless compression, with format .mp3 and .alac by using VADDs protocol. Simulation done with NS-2 version 2.35 to get the value of average packet delivery delay and average throughput. The simulation also using OneSim to determine the setting of variety speed and count of nodes. And then, the result of simulation will be assessed by reference of ITU-T Rec. G.1010. The result of simulation showed the value of average packet delivery delay has variety values, from the lowest value, are 91.382-170.982 ms for all audio file size, and has the value of variant throughput from 8.846 Mbps – 299.999 Mbps. Keywords: Artificial Intelligence, Expert System, Forward Chaining, Certainty Factor